Analysis of Current Status and Perspectives of Lithuania’s Managerial Potential - Mackevičius, Jonas (Ekonomika, 2008)
Monograph “Lithuania’s managerial potential. Its current status and perspectives for the future” is an interesting and valuable scientific work prepared by prof. hab. Dr. Albinas Marčinskas and doc. Dr. Danuta Diskienė. This monograph presents a complex analysis of current managerial potential in Lithuania and the competency of managers.The managerial potential in Lithuania is positioned along a linear scale, according to the factors affecting the total management capability levels. The main managerial potential component is the scientific component. The scientific component of managerial potential analysis the academic terminology in use, the field of interest of the young generation of management scientists, the field of interest of the academic community and the national management strategy.Management models and mechanisms are presented in monograph according to the different state and business organization management levels. The authors also presents comparative analysis of the system of Lithuanian management institutions with Estonia, Latvia and Finland same institutions. Most attention has been devoted to the analysis how managers themselves rate the main management functions - planning. organization. leadership, motivation and control and the level of their own managerial competency in realizing these functions.The monograph will be exceptionally useful to an academics and educators working in the management, economic, administration and as well as other fields, also for students of universities. Monograph is particularly helpful for members of Parliament and Government of Lithuania Republic.